Satisfaction: As a Mediation of Content Marketing, WOM, and Price Perception on Trust - Rahmawati, Dian; Santi, Ira Nuriya; Syarifuddin, Umar; Buntuang, Pricylia Chintya Dewi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study analyzes the influence of content marketing, word of mouth, and price perception on consumer trust through customer satisfaction as a mediating variable, with a case study on UMKM Ummi Home Baked Palu. Methodology/Approach: This quantitative research employed questionnaires distributed via Google Forms to 100 respondents using purposive sampling, focusing on customers who had made at least one purchase. A five-point Likert scale (1 = Strongly Disagree to 5 = Strongly Agree) was used. Data were analyzed with Structural Equation Modeling (SEM) using SmartPLS software. Results/Findings: The results show that content marketing, word of mouth, and price perception positively and significantly influence customer satisfaction, which then strengthens consumer trust. Word of mouth has the strongest effect, while customer satisfaction mediates and amplifies the relationship between the variables and trust Conclusions: Content marketing, word of mouth, and price perception significantly enhance customer satisfaction and trust, with satisfaction mediating and strengthening these relationships, underscoring the role of digital marketing strategies for MSMEs. Limitations: This study only examined one MSME, Ummi Home Baked Palu, in the culinary sector. Hence, results cannot be generalized to other MSMEs, as customer characteristics may differ. Contribution: The study contributes to academic development in management and business while offering practical implications for MSMEs in designing effective marketing strategies to enhance customer satisfaction and trust.